ANALISIS HASIL KONSELING INDIVIDU TERHADAP 5 ORANG SISWA YANG BERMASALAH DI SMP TRI BHAKTI PEKANBARU TAHUN AJARAN 2012/ 2013 - Yunita Sari; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
This study entitled "Analysis of Individual Counseling 5 People Against TheTroubled Students In Junior Tri Bhakti Pekanbaru Academic Year 2012/2013"shows the range of problems experienced by students, both physical healthproblems, family problems, problems with peers or problems in the field of studyso as to make the students feel very disturbed. The objectives of this study were:1) To determine how the general picture problems experienced by students injunior high 5 Tri Bhakti. 2) To know how is the alleviation of the problemsexperienced by students in junior high 5 Tri Bhakti. 3) To determine how students'opinions towards the achievement of individual counseling in the junior TriBhakti. 4) To determine how the description of the results of individualcounseling for students in junior high 5 Tri Bhakti. The population in this studywere junior grade students VIII4 Tri Bhakti Pekanbaru totaling 42 people, but asthe samples in this study consist of 5 people. The method used is the method ofaction Counseling. Of the implementation of individual counseling can bediscovered overview severe problems experienced by 5 students. After theimplementation of individual counseling students completed a questionnaire aboutstudents' responses after the implementation of counseling to determine thesuccess rate of individual counseling tersebut.Dari results of questionnaires filledout by 5 students can be seen that the level of success has been achieved, namelycounseling terentasnya problems experienced by 5 students. This is shown in theresults of data analysis and description based on the results of individualcounseling expressed by the students during the 5 counseling.Keywords: Individual Counseling, Counseling Results.